Loss of Specificity in Basal Ganglia Related Movement Disorders - Bronfeld, Maya; Bar‐Gad, Izhar (Frontiers in Systems Neuroscience, 2011)
The basal ganglia (BG) are a group of interconnected nuclei which play a pivotal part in limbic, associative and motor functions. This role is mirrored by the wide range of motor and behavioral abnormalities directly resulting from dysfunctions of the BG. Studies of normal behavior have found that BG neurons tend to phasically modulate their activity in relation to different behavioral events. In the normal BG, this modulation is highly specific, with each neuron related only to a small subset of behavioral events depending on specific combinations of movement parameters and context.. In many pathological conditions involving BG dysfunction and motor abnormalities, this neuronal specificity is lost. Loss of specificity (LOS) manifests in neuronal encoding of a larger spectrum of events and consequently a large overlap of movement-related activation patterns between different neurons. We review the existing evidence for LOS in BG-related movement disorders, the possible neural mechanisms underlying LOS, its effects on frequently used measures of neuronal activity and its relation to theoretical models of the BG. The prevalence of LOS in a many BG-related disorders suggests that neuronal specificity may represent a key feature of normal information processing in the BG system. Thus, the concept of neuronal specificity may underlie a unifying conceptual framework for the BG role in normal and abnormal motor control.